The Analysis of Financial Literacy and Its Impact on Investment Decisions: A Study on Generation Z In Jakarta - Novia Utami; Marsiana Luciana Sitanggang (Politeknik Negeri Bengkalis, 2021)
The influence of digitalization has extended across industries including the financial sector. Numerous innovations for investment have been launched while financial information has now become easily accessible, raising potential for Generation Z (Gen Z) to make investment. This study aims to understand financial literacy and investment behavior of Gen Z in Jakarta, Indonesia. Data were collected using quantitative approach, particularly through adoption of online questionnaire and convenience sampling technique. The relationship between financial literacy and investment decisions was then analyzed using Structural Equation Model regression - Lisrel statistical software. Finally, it was found that financial literacy significantly influenced investment decisions of Gen Z in Jakarta.